Odpowiedź :
x-cena filiżnki
y-cena tależyka
6x+6y=42 //:6
x+y=7
x=7-y
2x+6y=26zł
2(7-y)+6y=26
14-2y+6y=26
4y=12//:4
y=3 więc x=7-3=4
y-cena tależyka
6x+6y=42 //:6
x+y=7
x=7-y
2x+6y=26zł
2(7-y)+6y=26
14-2y+6y=26
4y=12//:4
y=3 więc x=7-3=4
6x+6y=42
2x+6y=26
6x+6y=42
2x=26-6y
6x+6y=42
x=13-3y
6(13-3y)+6y=42
x=13-3y
78-18y+6y=42
x=13-3y
36=12y
x=13-3y
y=3
x=13-3y
x=13-(3*3)
x=4
x-cena filiżanki
y-cena talerzyka
2x+6y=26
6x+6y=42
2x=26-6y
6x+6y=42
x=13-3y
6(13-3y)+6y=42
x=13-3y
78-18y+6y=42
x=13-3y
36=12y
x=13-3y
y=3
x=13-3y
x=13-(3*3)
x=4
x-cena filiżanki
y-cena talerzyka